Poverty Alleviation and Socio-Economic Improvement in Indonesia's Economic Development Plan - A'yunina , Qurotu; Himmati, Risdiana (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2024)
This study aims to examine the long- and short-term effects of five key socio-economic indicators—school enrolment rates, infant mortality rates, unemployment rates, the human development index (HDI), and the Gini ratio—on Indonesia’s per capita income from 1993 to 2022. Using the Error Correction Model (ECM) and data from Indonesia’s Central Statistics Agency (BPS), the research reveals that school enrolment, infant mortality, and unemployment rates significantly affect per capita income in the long term, while unemployment and HDI demonstrate significance in the short term. In contrast, the Gini ratio shows no statistically significant effect in either timeframe. These findings underscore the multidimensional nature of poverty alleviation and socio-economic progress, emphasizing the importance of targeted educational, health, and labor policies. The specific contribution of this study to the international research field lies in its comprehensive, multi-decade evaluation of economic development dynamics in a major developing economy. By integrating diverse social indicators into a longitudinal ECM framework, the study contributes novel empirical evidence on the complex causal pathways between inequality, human development, and income generation. It offers comparative insights for policymakers and researchers globally, particularly those working in contexts with similar demographic, institutional, and development challenges.